Hubungan Pengetahuan Remaja Tentang Kehamilan Dengan Sikap Pencegahan Seks Pranikah pada Remaja di Sekolah SMA 02 Kota Bengkulu - Imelda Lestari; Sulastri Sulastri; Danur Azissah RS (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Adolescence is an important transition phase in human life, namely the transition from childhood, sexual behavior is unhealthy among unmarried teenagers, increasing premarital sex which is still common in Indonesia due to lack of attention from parents, economics, free association, lack of knowledge about reproductive health and the environment. This study aims to determine the correlation between adolescent knowledge about pregnancy and attitudes towards preventing premarital sex in adolescents at SMA 02 Bengkulu City. This study uses a quantitative descriptive correlational method and a cross-sectional approach. The research population is all 476 female students of grades X and XI of SMA 02 Bengkulu City with a sample of 83 respondents selected using stratified random sampling. The research instrument is a questionnaire on adolescent knowledge about pregnancy and adolescent attitudes in preventing premarital sex. Data analysis was carried out univariately and bivariately using the Chi-Square test. The results showed that most respondents had knowledge about pregnancy in the categories of poor, adequate, and good. Poor scores were <56%, adequate scores were 56-75%, and good scores were 76-100%. The results of the square test showed a significant correlation between adolescent knowledge about pregnancy and attitudes toward preventing premarital sex among adolescents at SMA 02 in Bengkulu City (p <0.05). This study is expected to contribute to the development of nursing science, particularly community nursing and adolescent reproductive health. It also serves as a reference for educational institutions, the nursing profession, and schools in developing reproductive health education programs by optimizing adolescent knowledge about strategies for preventing premarital sex.